1984
DOI: 10.1080/00222895.1984.10735319
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Natural Prehension Movements

Abstract: Prehension movements were studied by film in 7 adult subjects. Transportation of the hand to the target-object location had features very similar to any aiming arm movement, that is, it involved a fast-velocity initial phase and a low-velocity final phase. The peak velocity of the movement was highly correlated with its amplitude, although total movement duration tended to remain invariant when target distance was changed. The low-velocity phase consistently began after about 75% of movement time had elapsed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

81
719
8
25

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,211 publications
(833 citation statements)
references
References 19 publications
81
719
8
25
Order By: Relevance
“…The reaching component of prehension is concerned with bringing the hand to the object to be grasped, whereas the grasping component refers to the opening and closing of the hand. This suggested division of labor stems from the seminal studies performed by Marc Jeannerod, about 25 years ago, which, for the Wrst time, reported details of the kinematics of prehensile movements (Jeannerod 1981(Jeannerod , 1984. Countless studies have addressed all kinds of aspects of prehension, taking this division in components as their starting point.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaching component of prehension is concerned with bringing the hand to the object to be grasped, whereas the grasping component refers to the opening and closing of the hand. This suggested division of labor stems from the seminal studies performed by Marc Jeannerod, about 25 years ago, which, for the Wrst time, reported details of the kinematics of prehensile movements (Jeannerod 1981(Jeannerod , 1984. Countless studies have addressed all kinds of aspects of prehension, taking this division in components as their starting point.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, with his Wrst systematic analysis of the kinematics of prehension, Jeannerod (1981Jeannerod ( , 1984 set the stage for a large number of studies of the control and coordination of reaching and grasping (for reviews, see Castiello 2005;Jeannerod 1988;MacKenzie and Iberall 1994). Jeannerod's proposal that a reaching (or transport) component and a grasping (or manipulation) component make up prehension was based on a number of arguments, such as anatomical arguments that diVerent muscles and Electronic supplementary material The online version of this article (doi:10.1007/s00221-007-0968-2) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal viewing conditions with visual feedback, maximum grip aperture (MGA) typically occurs ~75% relative to the total movement time (Glover, 2002). Numerous other studies have confirmed Jeannerod's (1984) division of prehension into two distinct and separable components (Dohl, Ostermann, Hefter & Freund, 2000;Shallice, Venable & Rumiati, 2005) with some authors demonstrating that these, furthermore, have distinct neural substrates (e.g. Cavina-Pratesi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…During the 1980s, Jeannerod (1981Jeannerod ( , 1984 demonstrated that manual prehension can be divided into two distinct neural and behavioural components -reaching and grasping.…”
Section: Introductionmentioning
confidence: 99%